Juridical Analysis of Law Enforcement Against Corruption Crimes in Indonesia - Youngky Fernando; Carl H. D. Steinmetz (The International Journal of Law Review and State Administration, 2025)
This study examines the legal framework and enforcement practices related to corruption crimes in Indonesia. Using a normative juridical approach, the research analyzes the statutory provisions governing corruption eradication, primarily Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, along with related regulations and judicial decisions. The findings indicate that although Indonesia has established a comprehensive anti-corruption legal framework, its implementation continues to face significant challenges. These include inconsistencies in law enforcement, political interference, limited institutional capacity, and varying levels of integrity among law enforcement officers. The study highlights the need for strengthening regulatory mechanisms, enhancing institutional coordination, improving transparency and accountability, and reforming law enforcement agencies to ensure more effective corruption eradication. The results are expected to contribute to the development of better legal policies and practical strategies for combating corruption in Indonesia.